2017
DOI: 10.1002/mame.201600451
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Energy‐to‐Electricity Conversion of Electron/Hole‐Transfer Agent‐Doped Poly(Vinylidene Fluoride) Nanofiber Webs

Abstract: Electrospun poly(vinylidene fluoride) (PVDF) nanofibers have shown novel property to convert kinetic energy into electricity. However, most of the PVDF nanofiber energy devices are based on pure PVDF. In this paper, the effect of small molecule doping on PVDF nanofiber diameter, β phase content, and mechanical‐to‐electrical energy conversion property is reported. Two chemicals, tri‐p‐tolylamine (TTA) and 2‐(4‐tert‐butylphenyl)‐5‐(4‐biphenylyl)‐1,3,4‐oxadiazole (Butyl‐PBD) which have electron‐ and hole‐transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…An electrospinning voltage of 20 kV was applied, and the distance between the grounded metal collector and the nozzle tip was fixed at 10 cm. The roller speed of electrospinning was 1000 rpm. , The graphic illustration of the preparation of F-BaTiO 3 /PVDF nanofibers is shown in Scheme .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An electrospinning voltage of 20 kV was applied, and the distance between the grounded metal collector and the nozzle tip was fixed at 10 cm. The roller speed of electrospinning was 1000 rpm. , The graphic illustration of the preparation of F-BaTiO 3 /PVDF nanofibers is shown in Scheme .…”
Section: Methodsmentioning
confidence: 99%
“…The roller speed of electrospinning was 1000 rpm. 25,26 The graphic illustration of the preparation of F-BaTiO 3 /PVDF nanofibers is shown in Scheme 1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These Schottky junction-based energy harvesters require no additional rectification circuit and favors the miniaturization and integration of the electronic devices, providing a new route for the self-powered devices and mechanical sensors [123]. Introduction of soft polymeric materials into energy harvesters will enable higher electric output and broaden their applications in flexible devices [79], [145], [146]. It was confirmed that Schottky contact was formed between p-type semiconductor PPy and metal Al and Ohmic contact was formed between the Au and PPy (Fig.…”
Section: B Energy Harvestermentioning
confidence: 99%
“…A lot of effort has been dedicated by many research groups to improve the electrical output performance of TENGs through new material syntheses, advanced structural designs, mechanical-coupling effects, and so on. Polymers, such as poly­(vinylidene fluoride) (PVDF), polypropylene (PP), polyimide, and poly­(phenylene sulfide), have attracted extensive interest due to their intrinsic advantages, including high breakdown strength, facile processability, low dielectric loss, and lightness, which make them an excellent option for the TENG application. Lu et al reported a novel and facile fabrication poling-free dynamic PVDF–Nafion polymeric piezoelectret generator with 14.6 V/cm 2 output. The weakness of their research was focused on the stimulated force and did not deal with the precharging onto their reported device resulted a small voltage outcome .…”
Section: Introductionmentioning
confidence: 99%